Phenethyl-4-ANPP: A Marginally Active Byproduct Suggesting a Switch in Illicit Fentanyl Synthesis Routes. Issue 4 (2nd April 2021) - Vandeputte, Marthe M; Krotulski, Alex J; Hulpia, Fabian; Van Calenbergh, Serge; Stove, Christophe P
Abstract: Profiling of the illicit fentanyl supply is invaluable from surveillance and intelligence perspectives. An important strategy includes the study of chemical attribution signatures (e.g., trace amounts of synthesis precursors, impurities/byproducts in seized material and metabolites in biological samples). This information provides valuable insight into the employed synthesis routes at the heart of illicit fentanyl manufacture (previously mainly the so-called Janssen or Siegfried methods), allowing to track and ultimately regulate crucial precursors. This report focuses on phenethyl-4-anilino- N- phenethylpiperidine (phenethyl-4-ANPP), a formerly unknown compound that was identified for the first time in a fentanyl powder sample seized in April 2019, followed by its identification in a biological sample in December 2019. Between 2019-Q4 and 2020-Q3, phenethyl-4-ANPP was detected in 25/1, 054 fentanyl cases in the USA. There are currently no reports on how this compound may have ended up in illicit drug preparations and whether its presence may have potential in vivo relevance. We propose three possible fentanyl synthesis routes that, when badly executed in a single reaction vessel, may involve the formation of phenethyl-4-ANPP. We hypothesize that the presence of the latter is the result of a shift in fentanyl synthesis routes in an attempt to circumvent restrictions on previously used precursors. Using a cell-based µ-opioid receptor recruitment assay, we show that the extent of MOR activation caused by 100 µM phenethyl-4-ANPP is comparable to that exerted by a roughly 100, 000-fold lower concentration of fentanyl (0.001 µM or 0.336 ng/mL). Negligible in vitro opioid activity, combined with its low abundance in fentanyl preparations, most likely renders phenethyl-4-ANPP biologically irrelevant in vivo. However, as clandestine operations are constantly changing shape, monitoring of fentanyl attributions remains pivotal in our understanding and control of illicit fentanyl manufacture and supply.